1998
DOI: 10.1080/08990229870781
|View full text |Cite
|
Sign up to set email alerts
|

The influence of rate of temperature change and peak stimulus duration on pain intensity and quality

Abstract: An important aspect of experimental pain research is that the assessment methods can investigate the different aspects of pain perception. The aim of the present study was to investigate the influence of rate of temperature change and peak stimulus duration on heat evoked pain intensity and quality. All stimuli were applied within the medial aspect of the anterior forearm. The rate of temperature change was varied from 1 to 16 degrees C/s without any effect on the pain threshold. The pain threshold decreased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Whether or not such differences have any effect on the PWT-H remains unclear. In previous studies on humans, Pertovaara (Pertovaara et al, 1996) and Nielsen and Arendt-Nielsen (Nielsen and Arendt-Nielsen, 1998) found no interaction between the rates of temperature change (1–16°C/s) and pain ratings, whereas Tillman and colleagues (Tillman et al, 1995) reported decreased heat threshold in human subjects when the rate of temperature change was greater. Moreover, it has been shown that the peak rates of discharge from C-fiber nociceptors increase with higher rates of temperature increase in humans (Yarnitsky et al, 1992) and monkeys (Tillman et al, 1995).…”
Section: Discussionmentioning
confidence: 93%
“…Whether or not such differences have any effect on the PWT-H remains unclear. In previous studies on humans, Pertovaara (Pertovaara et al, 1996) and Nielsen and Arendt-Nielsen (Nielsen and Arendt-Nielsen, 1998) found no interaction between the rates of temperature change (1–16°C/s) and pain ratings, whereas Tillman and colleagues (Tillman et al, 1995) reported decreased heat threshold in human subjects when the rate of temperature change was greater. Moreover, it has been shown that the peak rates of discharge from C-fiber nociceptors increase with higher rates of temperature increase in humans (Yarnitsky et al, 1992) and monkeys (Tillman et al, 1995).…”
Section: Discussionmentioning
confidence: 93%
“…This finding is in accordance with the results of Tillman et al [21] who evaluated how the thermal properties of the skin would affect the discharge of C fiber nociceptors (CMHs). This study concluded that due to the thermal inertia of the skin, the activation threshold temperature (at the skin surface) would increase with increasing stimulus ramp, this has been the debate of several publications [22-24]. Furthermore, the study by Tillman et al [21] also concluded that a higher stimulus ramp would produce a higher peak discharge of nociceptors (CMHs) due to the phasic properties of C fiber nociceptors.…”
Section: Discussionmentioning
confidence: 99%
“…Psychophysical thresholds for heat pain range from 40 to 49 for stimulation at glabrous and hairy skin sites with probes of different sizes and with widely varying ramp rates and stimulus durations (Hamalainen et al 1982;LaMotte 1984;LaMotte et al 1983;Morin and Bushnell 1998;Pertovaara et al 1996;Strigo et al 2000;Wahren et al 1989;Yarnitsky and Ochoa 1991). Most of the mean threshold values cluster between 43 and 46°C (Craig and Bushnell 1994;Dyck et al 1993;Hardy et al 1952;Harju 2002;Magerl and Treede 1996;Nielsen and Arendt-Nielsen 1998;Taylor et al 1993;Tillman et al 1995;Torebjork et al 1984;Verdugo and Ochoa 1992). In experiment 2 of this study, eVAS ratings of 10 represent a conservative estimate of threshold pain.…”
Section: Discussionmentioning
confidence: 99%